Das Wechselmodell - Reformbedarf im Kindschaftsrecht? 15. Göttinger Workshop zum Familienrecht 2017 - Schumann, Eva; Coester-Waltjen, Dagmar; Lipp, Volker; Veit, Barbara (Universitätsverlag Göttingen, 2018)
This volume brings together the papers of the 15th Göttingen Workshop on Family Law, which was held on the 20th October 2017 in cooperation with the joint project "Power and Powerlessness of Maternity". All in all eight contributions shed light on the currently controversial discussion about the so-called shared residence model from different perspectives: In addition to the constitutional basics, comparative and interdisciplinary approaches, all follow-up questions in maintenance, social and tax law are also dealt with. It becomes very clear that the deficits in the relevant laws can only be partially compensated by judiciary law and that the existing incoherencies can only be remedied rudimentary. In addition, well-founded proposals for reform are also presented.